Prevalence and correlates of young people’s sexual aggression perpetration and victimisation in 10 European countries: a multi-level analysis - Krahe, Barbara; Berger, Anja; Vanwesenbeeck, Ine; Bianchi, Gabriel; Chliaoutakis, Joannes El; Fernandez-Fuertes, Andres A.; Fuertes, Antonio; De Matos, Margarida Gaspar Aspar; Haller, Birgitt; Hellemans, Sabine; Izdebski, Zbigniew; Meijnckens, Dwayne; et al. (My University, 2015)
Data are presented on young people's sexual victimisation and perpetration from 10 European countries (Austria, Belgium, Cyprus, Greece, Lithuania, the Netherlands, Poland, Portugal, Slovakia and Spain) using a shared measurement tool (N = 3480 participants, aged between 18 and 27 years). Between 19.7 and 52.2% of female and between 10.1 and 55.8% of male respondents reported having experienced at least one incident of sexual victimisation since the age of consent. In two countries, victimisation rates were significantly higher for men than for women. Between 5.5 and 48.7% of male and 2.6 and 14.8% of female participants reported having engaged in a least one act of sexual aggression perpetration, with higher rates for men than for women in all countries. Victimisation rates correlated negatively with sexual assertiveness and positively with alcohol use in sexual encounters. Perpetration rates correlated positively with attitudes condoning physical dating violence and with alcohol use in men, and negatively with sexual assertiveness in women. At the country level, lower gender equality in economic power and in the work domain was related to higher male perpetration rates. Lower gender equality in political power and higher sexual assertiveness in women relative to men were linked to higher male victimisation rates.
Keywords: European Union; Multi-level correlates; Sexual aggression; Sexual victimisation; Young people